(untitled) (Kanun: Jurnal Undang-undang Malaysia, 2018)
There has been debate over whether Malaysian legal principles have ignored the concept of sovereignty which has been upheld by the Federal Constitution. Hence, this study aims to elaborate the concept of sovereigntyas stipulated in Article 181(1) of the Federal Constitution based on the indigeneity framework. This study employsthe qualitative legal history methodology. The data was collected from primary and secondary sources, as well as interviews. The results reveal that the sovereignty of the Malay rulers is based on Islamic teachings, and has never been abolished. This interpretation reveals the true position of the Malay rulers within the framework of the Federal Constitution. Thus, the legal principles and political system implemented in Malaysia have to be in line with this inherited concept of sovereignty. Keywords: Indigenous sovereignty, indigeneityframework, sovereignty of Malay Rulers, Malaysian sovereignty, Article 181(1) of the Federal Constitution.